Shadowing lemma for operators with chaotic behavior - Magreñán, Á. Alberto; Argyros, Ioannis K (Contemporary study of iterative methods: convergence, dynamics and applications, 2021)
Capítulo del libro "Contemporary study of iterative methods: convergence, dynamics and applications"
Keywords: shadowing lemma; chaotic behavior; dynamical systems; WOS(2)